Antiviral Activity of Novel Quinoxaline Derivative Against Herpes Simplex Virus Type 1, Human Cytomegalovirus, and Varicella-Zoster - Dr .Praphulla Kumar Singh; Dr. Babu Nand Choudhary (International Journal of Scientific Research in Chemistry, 2025)
Quinoxalines are nitrogen-containing heterocyclic compounds that are both widely recognized and significant. They form the ring complexity that consists of a pyrazine ring and a benzene ring. Distinctly substituted quinoxalines and related compounds, which are incorporated with an abundance of functional groups, constitute significant biological substances. A substantial quantity of studying has been focused towards this class. An assortment of innovative 5H-indolo-(2,3-b) quinoxaline derivatives that have a possibility to act as antiviral drugs. Plaque-reduction technique was implemented to evaluate the antiviral and cytotoxicity of a number of the synthesized compounds. The investigation employed the following methods: adjusting the virus by successive dilutions in the culture medium and assaying it in three separate batches on Vero the monolayers in each well of microtiter trays. The EC50, or the compound concentration necessary for minimizing virus-induced cytopathicity or viral plaque development by 50%, was used to express antiviral activity. Compound b demonstrated promising antiviral activity, while the majority of the compounds investigated exhibited cytotoxicity at a concentration of 160 ug/ml. The current study offered a comprehensive understanding of the synthesis of quinoxaline and its biological properties, as well as its antiviral properties against varicella-zoster virus, human cytomegalovirus, and herpes simplex virus type 1.